KURSI BERSUSPENSI BEBAS (INDEPENDENTSEAT) UNTUK MOBIL BERSUSPENSI KAKU (RIGID) - Wahyu Hidayat (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2009)
The seat-free suspension (independent seat) is in principle an ordinary chair to change the model by replacing the legs of the chair into the seat suspension system independent (independent seat) which aims to provide better passenger comfort. Free suspension seat designed to move smoothly and flexibly supported by springs and shock absorbers (shock absorber). The principle offree movement of the seat suspension is receiving reaction force car shocks then processed further by returning the expected reduction techniques can produce a more gentle oscillation motion. Independent suspension seat design that is applied by placing the swing arm (swing arm) and the shock absorber (shock absorber) as mechanical supporters. Key word: swing arm and shock absorber